Autekologi Begonia di Beberapa Lokasi di Pulau Flores - Sutomo Sutomo; Rajif Iryadi (Fakultas Kehutanan Universitas Gadjah Mada, 2021)
Human activities in forest areas such as over-harvesting of Begonia species without being balanced with their cultivation activities can threaten the existence of Begonia in nature. Autecological studies of species in their natural habitat are the initial activities for the conservation of plant species. The purpose of this study was to study the distribution of Begonia on Flores and environmental/ microclimate characteristics in several locations on Flores Island. The 10x10 m plots were placed with purposive sampling with a minimum interval of 50 m. Multivariate analysis using Canonical Corespondence Analysis (CCA) was employed to determine the effect of microclimatic factors on the composition of vegetation. Begonia kelimutensis is endemic in Kelimutu National Park, Flores lives at an altitude of 1,527 asl, at soil pH 5,8 and soil moisture of 75%, with a slope of 10 ° on the forest floor and light intensity 4,640 klux. In addition, five types of Begonia that we estimate have not been identified and two of them are identified as Begonia sumbawaensis Girm. and Begonia brangbosangensis Girm. Begonia kelimutuensis is distributed at a higher altitude than Begonia brangbosangensis. B. sumbawaensis is influenced by the slope factor while B. longifolia tends to be related to the air humidity factor. B. kelimutuensis is also often found living with Macaranga sp., and Litsea sp. B. brangbosangensis, also found near Homalanthus sp. and Calliandra callothyrsus.